2019
DOI: 10.1155/2019/2754927
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo MRI Tracking of Mesenchymal Stromal Cells Labeled with Ultrasmall Paramagnetic Iron Oxide Particles after Intramyocardial Transplantation in Patients with Chronic Ischemic Heart Disease

Abstract: Background While regenerative stem cell therapy for ischemic heart disease has moved into phase 3 studies, little is still known about retention and migration of cell posttransplantation. In human studies, the ability to track transplanted cells has been limited to labeling with radioisotopes and tracking using nuclear imaging. This method is limited by low resolution and short half-lives of available radioisotopes. Longitudinal tracking using magnetic resonance imaging (MRI) of myocardial injected cells label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…Mathiasen et al conducted the first contextual clinical study in human that evaluated the usage of dextran-coated TAT-conjugated IONP-labelled autologous BM-MSCs in intramyocardial transplantation of these cells in patients with chronic ischemic heart disease. Labelled MSCs could be tracked via MRI for up to 14 days after transplantation without compromising on safety [ 88 ].…”
Section: Ionps In Combination With Carbohydrates For Labelling Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathiasen et al conducted the first contextual clinical study in human that evaluated the usage of dextran-coated TAT-conjugated IONP-labelled autologous BM-MSCs in intramyocardial transplantation of these cells in patients with chronic ischemic heart disease. Labelled MSCs could be tracked via MRI for up to 14 days after transplantation without compromising on safety [ 88 ].…”
Section: Ionps In Combination With Carbohydrates For Labelling Mscsmentioning
confidence: 99%
“… • To assist incorporation into cells, IONPs could be cross-linked with a signal peptide/cell penetrating peptide that facilitate membrane translocation (e.g. HIV1- Tat protein) [ 36 , 88 ]. • Transfection agents (protamine sulphate, lipofectamine & poly-lysine) have been used to facilitate IONP entry into MSCs and enhance cell/tissue visualisation by MRI.…”
Section: Specific Caveats Associated With Ionp-labelling Of Mscsmentioning
confidence: 99%
“…In addition to the numerous and promising research results on monitoring stem cell-based treatment of cardiovascular diseases using IONP-loaded cells, first clinical studies have now been launched. In one trial, administration of ultra-small IONP-labeled autologous BM-MSCs after intramyocardial injection in patients with chronic ischemic heart disease was shown to be safe and the cells were detectable at the injection sites by MRI for up to two weeks after transplantation [ 252 ].…”
Section: Cardiovascular Tissue Regeneration and Engineeringmentioning
confidence: 99%
“…The MSC-HF trial assessed autologous BM-MSCs therapy in a larger number of patients with severe ischemic HF and an improvement in left ventricular end-systolic volume and ejection fraction was observed in patients treated with MSCs [ 116 ]. Recently, a published trial demonstrated that autologous BM-MSCs labelled with paramagnetic particles injected in the myocardium of patients with chronic ischemic heart disease was detectable up to 14 days after transplantation [ 117 ]. Results of the recent double-blinded multi-centered CONCERT-HF trial, that analyzed the safety and efficacy of transendocardial injection of autologous BM-MSCs along with c-kit positive cardiac cells (CPCs) showed a reduced incidence of major adverse cardiac events during the 12 months of follow-up in patients with ischemic cardiomyopathy.…”
Section: Msc-based Clinical Trials For Cardiomyopathy and Coronary Diseasementioning
confidence: 99%